Determinan Pencapaian Indikator Kapitasi Berbasis Kinerja pada Fasilitas Kesehatan Tingkat Pertama: Tinjauan Sistematik - Rizki Fadila; Katmini (LPPM Hang Tuah Pekanbaru, 2022)
The implementation of Capitation Based Performance payments has been carried out since 2016 but until now there are still many First Level Healthcare that have not been able to reach all the performance indicators. This study aims to analyze the determinants of the achievement of the Contact Number indicator, the Non-Specialized Case Referral Ratio, and the Controlled Prolanis Participant Ratio so that it is expected to know the effectiveness of the KBK implementation policy. This study uses a systematic review method using the PRISMA (Preferred Reporting Items for Systematic Review and Meta Analysis) guidelines. Literature searches were carried out using search engines: Research Gate, DOAJ, Google Scholar, and ScienceDirect so as to obtain 15 articles that were eligible for review. Overall, the main factors that influence the achievement of KBK are the availability of human resources, infrastructure, also knowledge of JKN participants. However, other factors such as the availability of funds, the existence of supporting policies and information systems and a commitment to fulfill the KBK indicators also affect the achievement of the KBK. In this case, the FKTP must carry out a workload analysis to count the number of human resources, fulfill infrastructure and routinely provide education to Prolanis participants.